Aggregation‐Induced Singlet Oxygen Generation: Functional Fluorophore and Anthrylphenylene Dyad Self‐Assemblies. Issue 3 (11th December 2017) - Kim, Sooyeon; Zhou, Yang; Tohnai, Norimitsu; Nakatsuji, Hirotaka; Matsusaki, Michiya; Fujitsuka, Mamoru; Miyata, Mikiji; Majima, Tetsuro
Abstract: The assembly of monomeric building blocks can manifest the display of new properties, including optical, mechanical, and electrochemical functionalities. In this study, we sought to develop a functional fluorophore self‐assembly that can generate reactive oxygen species only when aggregated. With an anthrylphenylene (AP) group, negatively charged and neutral fluorescein units form non‐fluorescent H‐aggregates in aqueous solution because of the weak intermolecular interaction between the anthracene and fluorescein moieties. In stark contrast, a boron dipyrromethene (BODIPY) and AP dyad produces two‐color‐emissive aggregates through the formation of an intermolecular charge‐transfer (CT) complex between the electron‐rich anthracene and electron‐deficient BODIPY moieties. Furthermore, to our surprise, the BODIPY and AP dyad aggregates generate singlet oxygen ( 1 O2 ) and photocytotoxicity upon excitation, indicating that the BODIPY–anthracene CT state favors an intersystem crossing process. Based on X‐ray crystallographic analysis, the lattice‐like molecular packing between the BODIPY and AP moieties was determined to bring about the unprecedented aggregation‐induced 1 O2 generation (AISG). Abstract : In aqueous solution, a boron‐dipyrromethene (BODIPY) and anthrylphenylene (AP) dyad forms a self‐assembly composed of an intermolecular charge‐transfer (CT) complex between BODIPY and AP moieties. Surprisingly, the BODIPY and AP dyad generates singlet oxygen ( 1 O2 ) upon excitation only when aggregated. Based on X‐ray crystallographic analysis, the lattice‐like molecular packing between the BODIPY and AP moieties was determined to bring about the unprecedented aggregation‐induced 1 O2 generation.